The Use of Puppet and Flashcard as Media in Teaching Vocabulary for Children with Special Needs - Wahyuni, Nining Candra (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2019)
Teaching vocabulary to children with special needs is not easy. There are some problems faced by teachers when they taught English vocabulary to the children with special needs, they did not pay attention to the teacher, and they lost their interest in English subject. This quasi experimental research attempted to describe what extent puppet and flashcard lead the children with special needs to the vocabulary development and to discuss students’ attitude towards puppet and flashcard media in learning vocabulary. The participants were students of eighth-grade of SLB Negeri Ungaran and SLB Widya Bhakti Semarang. There were two instruments; test and questionnaire. The results showed that the significance between post-test score of puppet group and flashcard group was 0.000 with significance 0.000 < 0.05. Furthermore, according to result of the questionnaire, students perception towards both media were positive, yet their interests in flashcard was higher than those in puppet media. It is suggested that flashcard media was more effective to be used in teaching vocabulary for children with special needs. Keywords: Puppet, Flashcard, Teaching Vocabulary, Quasi Experimental Research.